Ward D - McFadden, Freida ([Freida McFadden], 2023)
Medical student Amy Brenner is spending the night on a locked psychiatric ward. Amy has been dreading her evening working on Ward D, the hospital's inpatient mental health unit. There are very specific reasons why she never wanted to do this required overnight rotation. Reasons nobody can ever find out. And as the hours tick by, Amy grows increasingly convinced something terrible is happening within these tightly secured walls. When patients and staff start to vanish without a trace, it becomes clear that everyone on the unit is in grave danger. Amy's worst nightmare was spending the night on Ward D. And now she might never escape.